2015
DOI: 10.1126/science.aaa3650
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in amyotrophic lateral sclerosis identifies risk genes and pathways

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating neurological disease with no effective treatment. Here we report the results of a moderate-scale sequencing study aimed at identifying new genes contributing to predisposition for ALS. We performed whole exome sequencing of 2,874 ALS patients and compared them to 6,405 controls. Several known ALS genes were found to be associated, and the non-canonical IκB kinase family TANK-Binding Kinase 1 (TBK1) was identified as an ALS gene. TBK1 is known to bind to and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
754
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 850 publications
(790 citation statements)
references
References 61 publications
17
754
0
6
Order By: Relevance
“…From an empirical perspective, our findings suggest that re-sequencing in large samples is likely the best way forward in the face of the allelic heterogeneity imposed by the presence of rare alleles of large effect. Resequencing of candidate genes [77][78][79][80] and exomes [40,[81][82][83][84][85][86] in case-control panels have observed an abundance of rare variants associated with case status. Here we show that under a model of mutation-selection balance on the genic level, neither current single-marker nor popular multi-marker tests are especially powerful at detecting large genomic regions harboring multiple risk variants (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…From an empirical perspective, our findings suggest that re-sequencing in large samples is likely the best way forward in the face of the allelic heterogeneity imposed by the presence of rare alleles of large effect. Resequencing of candidate genes [77][78][79][80] and exomes [40,[81][82][83][84][85][86] in case-control panels have observed an abundance of rare variants associated with case status. Here we show that under a model of mutation-selection balance on the genic level, neither current single-marker nor popular multi-marker tests are especially powerful at detecting large genomic regions harboring multiple risk variants (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its roles of degradating foreign pathogens (xenophagy) (Wild et al, 2011) and binding to protein aggregates (Korac et al, 2013), OPTN1 is found in neuronal inclusions of patients affected by ALS and other neurodegenerative diseases (Schwab et al, 2012;Mori et al, 2012). The role of OPTN1 in ALS has been further elucidated by the recent discovery of loss of function mutations in TBK1 gene in familial ALS cases (Cirulli et al, 2015). The interaction between TBK1 and OPTN1 is a key factor in autophagy and inflammation (Maruyama et al, 2010;Maruyama and Kawakami, 2013;Thomas et al, 2013;Kachaner et al, 2012).…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%
“…Because intracellular components released during necroptosis stimulate inflammation and immune responses, it is thought that necroptosis contributes to the development/progression of neurodegenerative diseases. Recently, Cirulli et al [33] compared the whole exome sequences between ALS and control, and found that the non-canonical IκB kinase family TANK-binding kinase 1 (TBK1) was a gene associated with ALS by interacting with ALS-related proteins, optineurin (OPTN) and p62. Furthermore, Ito et al [34] demonstrated that OPTN inhibited dysmyelination and axonal degeneration through suppressing receptorinteracting kinase 1 (RIPK1) and the downstream subsets are preferentially elicited in ALS has been elusive.…”
Section: Necroptosis and Its Implications In Alsmentioning
confidence: 99%